Analisis Upaya, Faktor Pendukung dan Penghambat Pembelajaran Alquran dan Hadis di Madrasah Tsanawiyah Kota Padang, Sumatra Barat, Indonesia - Ahmad Lahmi; Aguswan Rasyid; Jummadillah Jummadillah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The purpose of this study is to analyze efforts, supporting, and obstacles factors to develop students' interest in learning Qur'an and hadith subject. This study employed a qualitative descriptive approach. Data obtained through interviews, observations, and documentation. Then, the data was analyzed through three phases including data reduction, data presentation, and conclusions. The research location was at Madrasah Tsanawiyah Aisyiah Belakang Olo, Padang City, West Sumatra, Indonesia. This study found two main points: First, efforts to increase participants' interest in the learning process including giving rewards, using varied learning methods, and explaining the ultimate goal of learning. Second, amid efforts to increase student interest in learning Quran-Hadith, there are supporting and inhibiting factors. Several supporting factors are adequate facilities and infrastructure, and high support from peer educators, as well as students. Moreover, the inhibiting factors including lack of students' enthusiasm for learning, family and social environment factors, and students' socio-economic factors.